Las imágenes de Japón en la obra de Amélie Nothomb - Yoshimoto, Yoshie (Escritura e Imagen, 2006)
Amélie Nothomb (Kôbe/Japan, b.1967) is one of the most internationally successful novelists today. Autobiographical novel is the key genre used by the author in more than a dozen of her published novels, concluding with the recent publication of Histoire de la faim (2004). In her conviction to have acquired the Japanese identity during her early childhood in that Far East country, the writer shows great confidence in grasping the Japanese culture in an intuitive, partial but essential way. She creates her personal Japanese myth according to her version of the Japanese religions, based on the empirical understandings and the collective imaginary repertoire. This creation is motivated by her strong desire to reconstruct her life with a coherence of meaning which reflects the importance the Sun-Rising country had for the formation of her identity, as well as the social paradox that is established between tradition and modernity in today’s Japan.